PERENCANAAN PENDIDIKAN PAI DI SEKOLAH TAHFIZH PLUS KHOIRU UMMAH PEKANBARU - Ahmad Husen; Zaid Kautsar; Mutmainah; Ami Latifah (UNISAN JURNAL, 2023)
This exploration expects to portray the picking up making arrangements for Islamic Strict Training at the Tahfizh In addition to Khoiru Ummah school in Pekanbaru. This examination utilizes a subjective methodology with a contextual investigation plan. The procedures used to gather information are interviews, member perception and documentation studies. Information examination and handling is completed by: 1) information decrease; 2) information show; and 3) make inferences or confirm. To get legitimate information, information and source triangulation is completed, implying that similar information is communicated from different sources. In light of the clarification above, it very well may be presumed that Khoiru Ummah Tahfizh In addition to School (STP) executes an "Islamic Religious Educational plan". Meaning: The Qur'an is the fundamental wellspring of information, as well as the reason for instructing youngsters' psyches and consummating kids' spirits. All information educated is joined with Islamic convictions, so all information is affirmed to be right prior to being instructed to kids. The educational plan is organized by youngsters' requirements in view old enough turn of events. All examples are intended to impact youngsters' way of behaving. Islamic Strict Training examples at STP Khoiru Ummah are called Islamic Strict Instruction. The picking up arranging is as per the following: Educational plan Course, Imparting confidence through manners of thinking, Developing a feeling of accommodation just to Allah SWT, Building connection to Sharia regulation, Ingraining confidence in the characteristics of Allah SWT. The idea of Allah SWT (Asmaul Husna) which causes understudies to have full attention to comply with the Shari'a autonomously and dependably, makes Rasulullah SAW a uswah throughout everyday life, doing the right love methodology as per the Shari'a, revering companions, tabiin, etc. Caliph, Ingraining high virtues, Imparting a feeling of initiative